ANALISIS PERBANDINGAN TINGKAT KERUSAKAN JALAN LENTUR MENGGUNAKAN METODE BINA MARGA DAN PAVEMENT CONDITION INDEX (PCI) - Zumalin, Zumalin; Guswandi, Guswandi; Lisya, Mutia (Politeknik Negeri Bengkalis, 2023)
This study aims to analyze the comparison of the level of road damage using the Bina Marga method and the Pavement Condition Index (PCI) at Jalan Sultan Syarif Kasim, Sungai Apit District. The degree of bending damage can provide an overview of the condition of the road infrastructure and must be accurately identified for effective maintenance planning. In this study, a field survey was conducted to collect data on flexible road conditions. The obtained data were then analyzed using the Highways and PCI methods. The results of the analysis compare the degree of damage to the flexible road produced by the two methods. The results of this study are expected to provide a better insight into the comparison of the extent of damage to flexible roads between the Highways and PCI methods. In accordance with the Bina Marga 1990 method if the UP value â‰¥ 7 is included in the periodic maintenance program category. The value of the rank on Jalan Sultan Syarif Kasim road, Teluk Masjid Village, Sungai Apit District, Siak Regency is 9.00. then it falls under the category of periodic maintenance. The average road condition value on Jalan Sultan Syarif Kasim (Sungai Apit) PCI method is 60.23 with fair rating (average)Â